Tren Politik Peringatan Darurat Garuda Pancasila Berlatar Belakang Biru di TikTok - Muna, Jazilatul; Dzikri, Irfa’i; Ramadhon, Laila Yusuf; Fatullah, Muhammad Rizky; Nisa , Pia Khoirotun (Innovative: Journal Of Social Science Research, 2025)
This study will analyze the phenomenon of social imitation triggered by viral content within the framework of mass communication sociology. The paper will discuss relevant theories, such as Bandura's social learning theory and the concept of social identity, to understand why individuals tend to imitate the behavior they see on social media. This study uses an interpretive paradigm that aims to understand the social meaning that arises from the phenomenon being studied, such as the viral content "Emergency Warning 2024". In this paradigm, researchers try to understand the perspectives of individuals involved in the social event, not just looking at the facts objectively. Based on this study, it is concluded that the analysis of the viral phenomenon "Emergency Warning" on TikTok includes a social imitation process involving factors of linkage, influence, and conformity. This viral content has various social, cultural, and psychological impacts, such as feelings of anxiety, fear, or euphoria, and forms collective behavior and public responses. In addition, TikTok as a social media platform plays an important role in accelerating the spread of social imitation through algorithms, the influence of celebrities or public figures involved, and the dynamics of online communities that strengthen this phenomenon.